DNAM-1 chimeric receptor-engineered NK cells: a new frontier for CAR-NK cell-based immunotherapy - Cifaldi, Loredana; Melaiu, Ombretta; Giovannoni, Roberto; Benvenuto, Monica; Focaccetti, Chiara; Nardozi, Daniela; Barillari, Giovanni; Bei, Roberto (Frontiers in Immunology, 2023)
DNAM-1 is a major NK cell activating receptor and, together with NKG2D and NCRs, by binding specific ligands, strongly contributes to mediating the killing of tumor or virus-infected cells. DNAM-1 specifically recognizes PVR and NECTIN2 ligands that are expressed on some virus-infected cells and on a broad spectrum of tumor cells of both hematological and solid malignancies. So far, while NK cells engineered for different antigen chimeric receptors (CARs) or chimeric NKG2D receptor have been extensively tested in preclinical and clinical studies, the use of DNAM-1 chimeric receptor-engineered NK cells has been proposed only in our recent proof-of-concept study and deserves further development. The aim of this perspective study is to describe the rationale for using this novel tool for anti-cancer immunotherapy.